Social Mendelism : genetics and the politics of race in Germany, 1900-1948 - Teicher, Amir 1978- (Cambridge University Press, 2020)
Mendel's laws and their application to humans, 1865-1913 -- Mendelism maturing : from experimental to interpretative framework, 1913-1933 -- Mendelism, purity and national renewal -- Annihilating defective genes : Mendelian consciousness and the sterilization campaign -- Mendelizing the sterilization law -- Mendelizing racial antisemitism -- Epilogue: Social mendelism beyond the Nazis.